Demonstration of a Reliable High Speed Phase-Change Memory Using Ge-Doped SbTe - Lee, Suyoun; Jeong, Jeung-hyun; Wu, Zhe; Park, Young-Wook; Kim, Won Mok; Cheong, Byung-ki (ELECTROCHEMICAL SOC INC, 2009)
For potential use in phase-change memory (PCM) devices, a Ge-doped SbTe (Ge-ST) was investigated with respect to both material properties and PCM device characteristics. Compared with Ge2Sb2Te5 (GST), the used Ge-ST (Ge5.3Sb77.7Te17) was characterized to have a lower melting temperature (814 K), a higher crystallization temperature (436 K), and a lower electrical resistivity in both amorphous and crystalline states. The Ge-ST devices have a much faster operation speed by about 1 order and consume less RESET power compared with the GST devices. Nevertheless, a higher RESET-programming current was required due to a lower dynamic resistance. Device reliability properties such as write/erase cycling endurance and data retention properties were also examined and found to be comparable to those of the GST devices, suggesting that the Ge-ST is a promising phase-change material for high speed PCMs. (C) 2009 The Electrochemical Society. [DOI: 10.1149/1.3133252] All rights reserved.
Keywords: MECHANISM; TE